Exploring Balanced Harvesting by Using an Atlantis Ecosystem Model for the Nordic and Barents Seas - Nilsen, Ina; Kolding, Jeppe; Hansen, Cecilie; Howell, Daniel (Frontiers in Marine Science, 2020)
“Balanced Harvesting” (BH) has been suggested as a possible strategy to meet the objectives of the Ecosystem Approach to Fisheries, ensuring a high sustainable yield while maintaining ecosystem structure and function. BH proposes a moderate fishing mortality in proportion to productivity spread across the widest possible range of species, stocks, and sizes in an ecosystem producing a sustainable and overall non-selective harvest. The Norwegian and Barents Seas have been subjected to moderate fishing pressure on commercial species, and elements of an ecosystem-based approach to management for many years, but not the fishing pattern proposed by BH. By using an Atlantis ecosystem model of the Nordic and Barents Seas, we investigated the effects of applying a BH regime to a region with existing successful fisheries management. This was done by running simulations with combinations of historic fishing pressure and fishing mortality rates proportional to 25% of the productivity of most species and sizes. The simulations were then compared to a control run where the historical fisheries were applied. The model results showed that implementing a BH regime in the Norwegian and Barents Seas would only produce marginal increases in total yields of currently commercially exploited stocks, likely because the Norwegian fisheries are already mostly well managed. However, expanding the fishery to include species that are not commercially exploited today did produce higher yields, especially on lower trophic levels. This study represents the first attempted examination of implementing BH based on productivity using an Atlantis ecosystem model, as well as the first investigation of BH in the Norwegian and Barents Seas. We use this model as a case study to identify the gains that species-based BH can be expected to give over well-implemented traditional fisheries management rather than simply comparing to an over-exploited system.